2023
DOI: 10.1002/mbo3.1376
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm assay for antimicrobial peptides combating the sulfate‐reducing bacteria Desulfovibrio vulgaris

Lena Stillger,
Lucile Viau,
Dirk Holtmann
et al.

Abstract: In medical, environmental, and industrial processes, the accumulation of bacteria in biofilms can disrupt many processes. Antimicrobial peptides (AMPs) are receiving increasing attention in the development of new substances to avoid or reduce biofilm formation. There is a lack of parallel testing of the effect against biofilms in this area, as well as in the testing of other antibiofilm agents. In this paper, a high‐throughput screening was developed for the analysis of the antibiofilm activity of AMPs, differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A significant reduction in bacterial load and a concomitant decrease in pro-inflammatory cytokines IL-1β, IL-6, and TNF-α was observed. The bacterium Desulfovibrio vulgaris and a corrosion biofilm model (using steel rivets as a surface for bacterial growth in a 96-well format) was developed by Stillger et al, who showed that AMPs S6L3-33 (bacterial reduction), bactenecin (total biomass reduction), and DASamP1 (biofilm inhibition up to 21 days) were the most useful anti-biocorrosive AMPs of those tested [137]. Finally, AMPs may be important in protecting foodstuffs from spoilage bacteria.…”
Section: Amp Modelsmentioning
confidence: 99%
“…A significant reduction in bacterial load and a concomitant decrease in pro-inflammatory cytokines IL-1β, IL-6, and TNF-α was observed. The bacterium Desulfovibrio vulgaris and a corrosion biofilm model (using steel rivets as a surface for bacterial growth in a 96-well format) was developed by Stillger et al, who showed that AMPs S6L3-33 (bacterial reduction), bactenecin (total biomass reduction), and DASamP1 (biofilm inhibition up to 21 days) were the most useful anti-biocorrosive AMPs of those tested [137]. Finally, AMPs may be important in protecting foodstuffs from spoilage bacteria.…”
Section: Amp Modelsmentioning
confidence: 99%